2018
DOI: 10.1007/s11605-018-3696-y
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Giant Hepatic Hemangioma: Single Center’s Experience with 144 Patients

Abstract: Giant hemangioma can be treated surgically with low incidence of morbidity and mortality. No statistical difference between enucleation and resection as regards surgical outcomes. In left lobe HH, HH located deeper in posterior hepatic segments and in multiple HH, hepatic resection is preferred. The size of the HH had significant impact intraoperative blood loss and operative time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…During the preliminary search, 132 articles were obtained. After reading the titles and abstracts and full texts and removing duplicate documents, a final number of 12 articles ( 8 , 12 – 22 ) were included in our study, which involved 1,384 patients ( Figure 1 ). Among them, 726 underwent pure hemangiomas enucleation and 658 were operated through hepatectomy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the preliminary search, 132 articles were obtained. After reading the titles and abstracts and full texts and removing duplicate documents, a final number of 12 articles ( 8 , 12 – 22 ) were included in our study, which involved 1,384 patients ( Figure 1 ). Among them, 726 underwent pure hemangiomas enucleation and 658 were operated through hepatectomy.…”
Section: Resultsmentioning
confidence: 99%
“…There are various treatment methods such as hemangioma enucleation, hepatectomy, hepatic artery interventional embolization, radiofrequency ablation, and others ( 6 , 7 ). When there are surgical indications such as large tumors, liver resection or hemangioma enucleation is the first choice of treatment ( 8 ). Hepatectomy is the traditional surgery for the treatment of hepatic hemangioma, but this surgery may be more traumatic than others because of the excessive removal of normal liver tissues, inaccurate treatment of liver sections, and a large amount of blood leakage.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have confirmed that hepatectomy and haemangioma enucleation are safe and feasible if the indications are properly controlled [ 2 , 5 , 7 , 9 , 10 ].…”
Section: Methodsmentioning
confidence: 99%
“… 3 , 4 Surgery is the most effective and widely accepted treatment for these symptomatic HH patients. 5 Rapid progress has continued in the technology and instrumentation 6 of laparoscopic surgery, which is mirrored by increasing acceptance by patients with HH, 7 even giant HH (defined here at >10 cm in diameter), 8 , 9 to undergo surgical resection with this technique. Nevertheless, certain obstacles remain problematic specifically relating to laparoscopic surgery for HH, 7 the most common and critical of which is potentially severe intraoperative bleeding that often results in conversion to laparotomy.…”
Section: Introductionmentioning
confidence: 99%